2016
DOI: 10.1007/s10926-016-9666-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prognostic Factors for Return to Work in Workers with Sub Acute and Chronic Low Back Pain

Abstract: Purpose We systematically reviewed the evidence on factors that predict duration of sick leave in workers after 6 weeks low back pain (LBP) related sick leave. We hypothesized that different factors affect the duration of the leave depending on the time away from work. Methods The review occurred in seven phases: (1) developing the central question, (2) conducting the literature search, (3) identifying relevant publications, (4) quality appraisal, (5) data extraction, (6) evidence synthesis, and (7) knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
158
1
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 68 publications
12
158
1
9
Order By: Relevance
“…Nurses with a full work capacity had a 77% higher trunk extension endurance compared to those with work modifications due to CLBP . Furthermore, a systematic review showed that functional status and physical demands may be important prognostic factors impeding return to work in those with CLBP . Even though causality between CLBP and muscle function cannot be determined, improving trunk muscle endurance may provide important training specificity, since it closely relates to occupational demands .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses with a full work capacity had a 77% higher trunk extension endurance compared to those with work modifications due to CLBP . Furthermore, a systematic review showed that functional status and physical demands may be important prognostic factors impeding return to work in those with CLBP . Even though causality between CLBP and muscle function cannot be determined, improving trunk muscle endurance may provide important training specificity, since it closely relates to occupational demands .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…Even though causality between CLBP and muscle function cannot be determined, improving trunk muscle endurance may provide important training specificity, since it closely relates to occupational demands . Periods of time away from work may lead to deconditioning towards work‐related tasks, and therefore may need to be improved to assist with task completion and return to work . Adequate levels of trunk endurance and overall strength appear to assist with ADLs and could be a prognostic factor for return to work, and should be considered in those with CLBP with high physical requirements.…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…The reference lists of included studies and related systematic reviews [22,[31][32][33][34][35][36] will be searched. Citation searching of questionnaires for depressive symptoms that have been utilized in LBP populations will also be conducted: Center for Epidemiologic Studies Depression Scale, Beck Depression Index, Patient Health Questionnaire-9, and Depression Scale of the Hospital Anxiety and Depression Scale.…”
Section: Study Designs/characteristicsmentioning
confidence: 99%
“…To our best knowledge, a systematic review examining the impact of depressive symptoms and depression on health care utilization in adults with LBP has not been previously conducted. Previous systematic reviews examining depressive symptoms and depression as prognostic factors affecting clinical or work-related outcomes for LBP require updating, as literature searches were completed before or up to early 2016 [22,[31][32][33][34][35][36]. Of these, the reviews with most recent literature searches were conducted by Alhowimel [22].…”
Section: Introductionmentioning
confidence: 99%
“…The high socioeconomic burden and healthcare utilization associated with chronic pain are therefore often reduced to secondary outcomes . When pain becomes chronic, return to work (RTW) is negatively associated with a delay in referral to treatment, socioeconomic status, attorney involvement, and worker's compensation are . Several studies have shown that unemployment and absenteeism are “negatively associated with quality of life, depression and generally poor health outcomes” .…”
Section: Introductionmentioning
confidence: 99%